Modular synthesis of allyl vinyl ethers for the enantioselective construction of functionalized quaternary stereocenters. Issue 106 (2nd November 2016) - Muthusamy, Gopinathan; Pansare, Sunil V.
Abstract : A flexible synthesis of allyl vinyl ethers, precursors of functionalized quaternary stereocenters, was developed by employing a regioselective Petasis olefination of haloallyl oxalates and subsequent cross-coupling with alkyl- and aryl boronic acids. Abstract : A concise synthesis of 2- t -butoxycarbonyl allyl vinyl ethers by regioselective Petasis methylenation and stereoselective Suzuki–Miyaura cross-coupling reactions of iodoallyl t -butyl oxalates was developed. Ethers with a terminally unsubstituted vinyl group and a terminally disubstituted allyl portion are readily accessible by this method. The enantioselective Claisen rearrangement of representative allyl vinyl ethers was examined.